Surviving our catastrophes : resilience and renewal from Hiroshima to the COVID-19 pandemic - Lifton, Robert Jay, 1926- (The New Press, 2023)
"A powerful rumination on how we can draw on historical examples of "survivor power" to understand the upheaval and death caused by the COVID-19 pandemic and collectively heal"--